Addition of Rodent Tuber Leaf Flour (Typhonium Flagelliforme) In Growth Period Peking Duck - Andhika Putra; Tengku Gilang Pradana; Alfath Rusdi; Media Agus Kurniawan; Purwosiswoyo Purwosiswoyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Utilization of local resources to support livestock production in the research location includes rodent tuber leaves found in many areas palm plantations, which have good nutritional content, but have high crude fiber. This study aims to find out the effect of Rodent Tuber Leaf Flour on rations during peking duck growth. The research method used an experimental method with completely randomized design (CRD) consist of 4 treatments and 5 replications, where treatment P1 = control ration feed, P2 = treatment feed with 5% rodent tuber leaves, P3 = treatment feed with 10% leaves rodent tuber and P4 = treated feed with 15% rodent tuber leaves, parameters count was feed consumption, body weight gain and feed conversion. The results showed significant effect results on ration consumption, the results of body weight gain showed significant effect results and in feed conversion showed significant effect results. The conclusion is the addition of rodent tuber leaf flour to the rations of Peking ducks at the level of 10% in the ration increases ration consumption and body weight gain, and increases the efficiency of ration conversion.